THE EFFECT OF ZISWAF FUND RECEIPTS, ROE, GWM ON NPF GROSS WITH FIRM SIZE AS MODERATING VARIABLE IN ISLAMIC BANKING IN INDONESIA PERIOD 2018-2023 - 'Ainunnaja, Isna; Budianto, Eka Wahyu Hestya (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2024)
Abstract: This study seeks to explore the influence of ZISWAF fund receipts, ROE, and GWM on Gross NPF in Islamic financial institutions, with firm size acting as a moderating factor. The research also explores strategies to address these issues. The sample consists of 115 companies in the financial sector registered with the OJK since 2018.Q1 to 2023.Q3. Purposive sampling was employed for data collection. MRA and panel data regression analysis were performed using Eviews 12 software.The findings indicate that ZISWAF fund receipts, ROE, and GWM significantly influence Gross NPF in the financial sector during the specified period. Additionally, firm size moderates the effects of ZISWAF fund receipts, ROE, and GWM on Gross NPF in the financial sector from 2018.Q1 to 2023.Q3. Keywords: ZISWAF Funds, ROE, GWM, NPF Gross, Firm Size